Olson E. T. Was I Ever a Fetus? / trans. from Engl. V. A. Sermaksheva - V. A. Sermaksheva (Омский научный вестник: Серия "Общество. История. Современность")
The Standard View of personal identity says that someone who exists now can exist at another time only if there is continuity of her mental contents or capacities. But no person is psychologically continuous with a fetus, for a fetus, at least early in its career, has no mental features at all. So the Standard View entails that no person was ever a fetus-contrary to the popular assumption that an unthinking fetus is a potential person. It is also mysterious what does ordinarily happen to a human fetus, if it does not come to be a person. Although an extremely complex variant of the Standard View may allow one to persist without psychological continuity before one becomes a person but not afterwards, a far simpler solution is to accept a radically non-psychological account of our identity